The Diversity and Abundance of Termites (Order: Isoptera) at Altitude 200 M ASL Karst Area Southern Gombong, Kebumen Regency - nufus, Wafiyyatun; Pratiknyo, Hery; Sukarsa, Sukarsa (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
Termites are social insects that have a very wide distribution. The termites in the forest ecosystem have many species and feeding habits, it can be said that diversity and abundance determine the role in the termite ecosystem. The termite are very important as a mediator for decomposition of the ecosystem of karst area. Therefeore, the aim of this study was to determine the diversity and abundance of termites in kasrt area at an altitude of 200 m asl Southern Gombong, Kebumen Regency. The study was conducted in a survey method and arranged as follows, in which 20 sub transect size of 5 m x 2 m as repetition and the termite was found is taken to vial bottle with alcohol 70% for identification. The data analysis using F test and continue with the LSD analysis. The study was obtained three diversity of termite in the karst area, there are M. gilvus, M. inspiratus and S. javanicus. The abundance of termite was obtained by M. gilvus is highest than the other termite with percentage of 90% while the abundance of termites based on plot was obtain in plot 1 with percentages 30,4%.